Agricultural policy reforms and regional market integration in Malawi, Zambia, and Zimbabwe - Valdes, Alberto; Muir-Leresche, Kay (International Food Policy Research Institute, 1993)
Economic growth in developing countries has generally slowed since the early 1980s. In many countries in Sub-saharan Africa, per capita income has even declined. External developments have had an adverse effect, as the slowdown in world economic activity and deteriorating terms of trade for most agricultural commodities have posed severe difficultues for many developing countries. More important, however, inappropriate domestic policies have been increasingly recognized as a major culprit. This has led to the adoption of various programs of macroeconomic and sectoral policy reforms, generally aimed at achieving macroeconomic stability and a satisfactory rate of economic growth. Among southern African countries, there has also been keen interest in promoting regional market integration.